Pengaplikasian R dalam menyelesaikan sistem persamaan liniear tiga variabel menggunakan metode Gauss - Waliyal Huzan; Rendy Rionaldo (Papanda Publisher, 2026)
This study aims to compare the accuracy of solving a Three-Variable System of Liniear Equations (SLS) using the Gauss method manually and with the assistance of R software. A quantitative comparative design was employed, involving ten students from the Information Technology Study Program who solved the same SLE problem manually and using the soulve() function in R. Data were analyzed using a paired sample t-test at a 5% significance level to determine whether there was a significant difference between the two methods. The results show that the t-calculated value exceeds the t-table value, indicatinga significant different in accuracy. The use of R produced substantially higher accuracy due to the soulve() function’s optimized matrix computation, which minimizes arithmetic erros commonly found in manual calculation. These findings demonstrate that integrating R software into Liniear Algebra learning enhances student’s accuracy, efficiency, and conceptual understanding when solving three-variable SLEs.